Determination of lithium toxicity by apoptosis and different biomarkers on Carassius auratus (Linn.) tissues (Indian Journal of Experimental Biology (IJEB), 2023)
The widespread use of lithium, one of the heavy metals, in many industrial processes has resulted in significant contamination of groundwater and surface water. Such contaminants enter into the food chain ecosystem and thereby challenge humans health, In fish, absorption of lithium is most likely through the default Na channel in the gills and muscle. In fish gills, the cell type primarily responsible for the regulation of atoms and ionic regulation are mitochondria-rich cells, also known as chloride cells. Here, we studied the effect of lithium toxicity on tissues of Goldfish, Carassius auratus (Linn.) as a model. We did spectrophotometric measurements to determine the effects of lithium dose (50 mg/L) in C. auratus at different times (24, 48, 72 and 96 h) of lithium dose. The results have shown LiCl induced alterations in CAT, SOD and GPx enzyme activities in the tissues of C. auratus depending on the concentration and duration of action at MDA, 8-OHdG and caspase-3 levels. Further, we observed increased levels of 8-OHG, modifications of nucleotides, and DNA damage due to lithium toxicity.